Statin-Induced Necrotizing Autoimmune Myopathy: Two Case Report - Rocha, Diana Isabel (2023)
Statin-induced necrotizing myopathy is an immune-mediatedadverse effect that, although rare, should be suspected in the presence of myalgia and rhabdomyolysis, which can persist even after discontinuation of the drug. The prognosis isgenerally favourable, requiring immunosuppressive therapy inmost cases. We present two clinical cases with histologicaldocumentation, the second with greater severity requiring therapy with intravenous immunoglobulins. Statins are often prescribed for their role in reducing cardiovascular risk, so clinicians need to be aware of this entity so that treatment can be quickly started, preventing sequelae. We underline the importance of prompt initial diagnosis andtimely target treatment beginning: Eculizumab, the only oneavailable in Portugal at the moment. Plasmapheresis and/orrenal replacement therapy must be considered case by case.